Pengaruh Latar Belakang Keluarga Broken Home terhadap Minat Belajar Siswa Madrasah Tsanawiyah: The Influence of Broken Home Family Background on Learning Interest Among Madrasah Tsanawiyah Students - Suryani, Asri; Wahyudi, Benny; Malik, Muhammad Ibnu; Nurpriatna, Ade; Hasanah, E.; Ismatullah, Ade (Risalah Kharisma, 2025)
Family involvement has a major impact on children's motivation to learn. Good personality is usually shown by children who are raised in harmonious and intact homes. The purpose of this study was to determine the state of broken home families, the level of learning interest among students, and the relationship between the two at MTs Hikmatunnidzom Gunungguruh Sukabumi. This study used an experiment as its methodology, using a sample of 20 students from families with broken homes. Data collection techniques included interviews, observations, and surveys. The relationship between students' learning interest and families with broken homes was ascertained by quantitative analysis of the data. Many students at MTs Hikmatunnidzom Gunungguruh Sukabumi rarely live with their parents, according to the data, which shows that broken home families are a relatively rare occurrence. Students' learning interest is in the sufficient group. However, based on statistical analysis, if the rxy value (0.38) < rtable (0.468), then Ho is accepted, which indicates that students' learning interest is not influenced by a history of broken home families. Thus, at MTs Hikmatunnidzom Gunungguruh Sukabumi there is no correlation between students' interest in learning and the condition of broken home families.